EXPERIENCE IN THE USE OF MINIMALLY INVASIVE OPERATIONS IN ACUTE APPENDICITIS - Мугатасимов, Игорь Григорьевич; Алексеев, Андрей Михайлович; Валиахмедова, Кристина Валерьевна; Берсенев, Андрей Александрович; Чернявский, Сергей Сергеевич (Medicine in Kuzbass, 2019)
The study included 1520 patients with acute appendicitis who were treated in two large surgical hospitals in Novokuznetsk from 2010 to 2014 inclusive, as well as from June 2016 to June 2018. The aim of the study – assess the immediate results of appendectomies and to develop ways to prevent infection of the surgical intervention area Materials and methods. A method of prevention infection of the surgical intervention area on the basis of cytokineproducing using recombinant IL-2. A comparative assessment of time intervals was carried out according to the following criteria: the number of performed minimally invasive appendectomies, gender and age of patients. Evaluation of the effectiveness of antibiotic prophylaxis and the use of prevention infection of the surgical intervention area. Results. Obtained from laparoscopic appendectomy performed in 1075 (70.7 %) patients. The use of laparoscopic access in the treatment of acute appendicitis reduces the number of infectious complications to 4.2 %. Antibiotic prophylaxis does not fully solve the problem of development infection of the surgical intervention area in patients with acute appendicitis. Conclusion. Local and regional use of rIl-2 reduces the risk of developing IOCs in patients with acute appendicitis to 2.9 % of cases.